Emissões de amônia e óxido nitroso após aplicação de dejetos de bovinos na semeadura e ureia em cobertura na sucessão trigo/milho em plantio direto - Tonetto, Felipe (2016)
The application of dairy slurry (DS) to the soil surface in no-till can result in the ammonia (NH3) and nitrous oxide (N2O) emission to atmosphere, with negative repercussions both agronomical and environmentally. The magnitude of these emissions may reduce the expected benefits from the agricultural use of dairy slurry as a nitrogen (N) source to crops. The objective of this work was to evaluate the N2O and NH3 emission according to the method of DS application in soil (surface broadacast vs. shallow injection), with and without the use of the nitrification inhibitor dicyandiamide (DCD) at sowing, associated with the application of urea sidedress. The work was developed in the experimental area of the Department of Soils of the Federal University of Santa Maria (UFSM), in a Hapludalf. The experiment was established in a randomized complete block design with four replications and plots with dimensions of 33 m2 (5,5 m x 6 m). The treatments were: T1- Control; T2- Surface application of mineral fertilization in sowing and urea sidedress (NPK + U); T3- DS broadcast and urea (DSs + U); T4- DSs broadcast with DCD and urea (DSs + DCD + U); T5- DS injected and urea (DSi + U) and T6- DS injected with DCD and urea (DLBi + DCD + U). The N2O evaluations were performed using static chambers and the ammonia was evaluated in the wheat through semi-open static chambers and in the corn through semi-open collectors. Dairy slurry injection in sowing increase N2O emission in 2,198 g ha-1 (56%) in relation to the traditional way of urea use, applying 1/3 of the N at sowing and 2/3 in sidedress. The DCD addition to dairy slurry did not affect the annual N2O emission when the dairy manure was applied on the soil surface in sowing of wheat and corn, compare with exclusive use of urea. The results showed that the lower N2O emission occurred with the use combined of DCD with dairy slurry before its injection into the soil, in sowing of the cultures. NH3 cumulative emissions did not differ between the application of dairy manure in pre-sowing associated with sidedress urea from the traditional mode of exclusive use of urea. The results suggest that N2O and NH3 emissions factors preconized by IPCC are overestimated for dairy manure for Southern Brazil.